Sources of the Asian currency crisis - Abdul Majid, Muhd Zulkhibri; Yusoff, Mohammed (Ashgate Publishing Limited, 2005)
This study examines the determinants of currency crises in Malaysia, Thailand,Indonesia, and the Philippines using quaterly panel data. The results indicate that reserve inadequacy, deteriorating trade balance, increases of banks'claims on private sector, and misalignment of exchange rate will increase the probalilty of a speculative attack. The results also suggest that currency crises could be contagious.